Selective Mixing of a Symphonic Orchestra Recording - KLECZKOWSKI, Piotr (Archives of Acoustics, 2008)
The selective method of mixing of sounds, developed by the author, has been applied to a multitrack recording of a symphonic orchestra. This method, still under development, offers a slight increase in the perceived clarity of recordings when compared to normal mixing. Fifteen stereophonic tracks of a symphonic orchestra recording have been processed. At first, the algorithm used earlier by the author for the recordings consisting of five and six tracks was used. After considering the remarks of listeners of informal listening tests, two modifications of that algorithm, specific for the recordings of a symphonic orchestra, have been introduced. Both modifications consisted in specific processing of selected groups of the tracks. During the final listening test, 32 untrained listeners compared the normal mix with the basic algorithm and with the two advanced algorithms of selective mixing. The advanced algorithms worked better than the basic one, indicating the direction for further improvement.